2010
DOI: 10.1111/j.1365-3156.2010.02505.x
|View full text |Cite
|
Sign up to set email alerts
|

Low retention of HIV‐infected patients on antiretroviral therapy in 11 clinical centres in West Africa

Abstract: SummaryObjective-To study factors associated with the probability of retention in antiretroviral therapy (ART) programs in West Africa. Methods-TheInternational epidemiologic Databases to Evaluate AIDS (IeDEA) in West Africa is a prospective, operational, observational cohort study based on collaboration between 11 cohorts of HIV-infected adult patients in Benin, Côte d'Ivoire, Gambia, Mali and Senegal. All patients aged 16 and older at ART initiation, with documented gender and date of ART initiation, were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
54
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 19 publications
12
54
4
Order By: Relevance
“…However we must note that more females than males were lost to follow up in this study. This differs from other studies in a number of settings that find male sex a predictor of poor retention [34] (Geng retention) including in a multisite study from West Africa [35], South Africa [36], Western Kenya [37] and Malawi [38].…”
Section: Discussioncontrasting
confidence: 84%
“…However we must note that more females than males were lost to follow up in this study. This differs from other studies in a number of settings that find male sex a predictor of poor retention [34] (Geng retention) including in a multisite study from West Africa [35], South Africa [36], Western Kenya [37] and Malawi [38].…”
Section: Discussioncontrasting
confidence: 84%
“…These include syntheses of reasons for stopping treatment 10,11 and pooled analyses of data from multiple cohorts in a region 12 . Quantitative results have generally been similar to ours, though several authors have noted that the definition of loss can influence estimated rates 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis on South African cohorts suggested that although trends in early (at 12 months) mortality have declined over time from 2002-2007, the rate of loss to follow-up has increased [59,69]. Loss to follow-up at 6-12 months is around 25% in several African cohorts [70][71][72][73][74]. Further, the loss to follow-up is highest in those with lower baseline CD4 þ cell counts who are at greater risk of death [53 ,64,75-77].…”
Section: Cd4r Counts At Combination Antiretroviral Therapy Initiationmentioning
confidence: 99%